NSAIDs in the treatment of patients with primary dysmenorrhea - V V Korennaya (IP Berlin A.V., 2015)
Primary dysmenorrhea is one of the most common forms of menstrual disorders in young age. This often leads to disablement of patients for several days and requires high-speed and efficient preparations. The first line of therapy in primary dysmenorrhea is considered to be the nonsteroidal anti-inflammatory agents (NSAIDs). When persistent menstrual dysfunction occurs, leading to recurrent episodes of pain, perhaps the appointment of combined hormonal contraceptives can be considered as the best method. The effectiveness of alternative treatments, although confirmed by a number of researchers, it lags behind the traditional approaches. According to recent data, the highest efficiency in the treatment of primary dysmenorrhea was shown by NSAID ibuprofen 400 mg.